Implications of the 1920 Trianon Peace Treaty for Egypt and its Consequences on Bilateral Relations with Hungary: مصر ومعاهدة تريانون: آثارها على العلاقات الثنائية مع المجر - Prantner, Zoltán; Abdallah, Abdel-Ati Al-Naggar (Études sur la Région Méditerranéenne, 2023)
Based on the press, archival, and online materials we have researched so far, it can be concluded that Egyptians were already deeply involved in the events, news, analysis and commentary of the Paris Peace Conference since 1919. This special interest was also evident in the Trianon Peace Treaty. Egyptian writers have expressed sharply critical views on the unjust peace dictate in newspaper articles and analysis dumps from its signing to the present day. In this paper, we will first provide a brief insight into Austro-Hungarian-Egyptian relations prior to the World War I, and then explain the circumstances of the conclusion and signing of the Treaty on Trianon. We also discuss the peace negotiations and the contemporary and current Egyptian echoes of the signed peace treaty. We will also discuss the consequences of the Trianon Peace Treaty for relations between the two countries, and what links the Arab media have suggested between Prime Minister Viktor Orbán’s statements and the peace treaty of a century earlier.